APPLICATION OF PAYMENTS IN FAST FOOD RESTAURANT USING MICROSOFT VISUAL FOXPRO 9.0 - Wita Haryanti; MS Wulandari Skom, MMSI (Jurnal Sistem Informasi, 2010)
Microsoft Visual FoxPro 9.0 is a software used for data processing. Data processingdone with the database as a place to store data.As payment restaurants in general also has relationships with exit and entry of articlesand reports. To control the exit and entry of goods and facilitate in making the reportused language Microsoft Visual FoxPro 9.0.With this application, it is expected to be useful in improving the performance ofemployees. This is because the performance of the employees can not be separatedfrom data and information quickly and accurately so that the time it takes to be a littlemore.